EDUKASI DAN APLIKASI TEKNOLOGI PROBIOTIK BERBAHAN BAKU LOKAL BAGI PEMBUDIDAYA IKAN AIR TAWAR EKONOMIS PENTING - Fazril Saputra; Yusran Ibrahim; Dini Islama; Zulfadhli Zulfadhli; Mahendra Mahendra; Faliqul Isbah; Anhar Rozi; Samsul Bahri (Universitas Teuku Umar, 2022)
Beutong District is one of the sub-districts in Nagan Raya Regency with an area of 1,017.32 Km2. The topography of Beutong District supports the cultivation of freshwater fisheries. The purpose of this service activity is to educate and apply the provision of probiotic technology made from local ingredients to increase production performance and the health status of economically important freshwater aquaculture fish. The method used in this activity is an educational method and application of probiotic technology made from local raw materials for economically important freshwater fish. The program begins with educating about the concept of using probiotic technology made from local ingredients, how to make probiotics made from local ingredients, methods of giving probiotics made from local ingredients and ending with training on good fish farming. Monitoring and evaluation will also be carried out to see the level of independence of fish farmers in applying the science and technology that has been taught and the sustainability of the program as well as the obstacles during this program. The result of this service activity is that probiotic technology made from local ingredients is effectively applied to economically important freshwater fish farming.